Rab27a co-ordinates actin-dependent transport by controlling organelle-associated motors and track assembly proteins - Noura Alzahofi (Nature Portfolio, 2020)
Melanosomes traffic along F-actin in melanocytes. Here, the authors show that Rab27a coordinates SPIRE/FMN actin assembly and MyoVa motor proteins to generate a cell-wide actin/myosin network that links melanosomes and allows the collective activity of these force generators to drive their traffic.